1991
DOI: 10.1007/bf01319699
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of photosynthesis by ultraviolet radiation as a function of dose and dosage rate: Results for a marine diatom

Abstract: Abstract. The effects of ultraviolet radiation on phytoplankton are usually described as a function of dose (J m-2, weighted appropriately). Experiments conducted in 1988 and 1989 on a marine diatom, Thalassiosira pseudonana (Clone 3H), demonstrate that during lightlimited photosynthesis in visible radiation, the inhibition of photosynthesis by supplemental ultraviolet radiation (principally UV-B: 280 to 320 nm) is a function ofirradiance (W m-2) as well as of dose: for equal doses of UV-B, a relatively short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
180
8
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(195 citation statements)
references
References 39 publications
6
180
8
1
Order By: Relevance
“…For the Xenon-Arc lamp, two example spectra from the present study are given: Xe lamp þ WG280, the treatment with the most short-wavelength UVR (long dashes), and Xe lamp þ WG320, a treatment with an intermediate level of UVR (short dash and dots). The spectrum for FS40 UV-B lamp was filtered by cellulose acetate (thin line, modified from Cullen and Lesser, 1991).…”
Section: Experimental Setup and Pigment Analysismentioning
confidence: 99%
“…For the Xenon-Arc lamp, two example spectra from the present study are given: Xe lamp þ WG280, the treatment with the most short-wavelength UVR (long dashes), and Xe lamp þ WG320, a treatment with an intermediate level of UVR (short dash and dots). The spectrum for FS40 UV-B lamp was filtered by cellulose acetate (thin line, modified from Cullen and Lesser, 1991).…”
Section: Experimental Setup and Pigment Analysismentioning
confidence: 99%
“…The inhibition of phytoplankton photosynthesis by UV is one effect of major ecological significance, although it is not the only type of damage that can occur (Vincent and Neale 2000 and references therein). Numerous studies have shown that UV-B and UV-A inhibit photosynthesis in natural populations (Helbling et al 1992;Smith et al 1992;Behrenfeld et al 1993;Neale et al 1994) and cultures (Cullen and Lesser 1991;Cullen et al 1992;Neale et al 1998a).…”
mentioning
confidence: 99%
“…5) seems to indicate surprisingly low influence of dynamic adaptation. This could occur if the rate of dynamic adjustment (time period to attain steady-state) was much faster in the Lake Lucerne assemblage than the 30 min observed by Cullen and Lesser (1991), also if any lag in inhibition is matched by a corresponding lag in recovery.…”
Section: Discussionmentioning
confidence: 97%
“…Time course of calculated parameters of UV-inhibition in bottles with high UV (quartz, solid line) and with low UV (Duran, dotted line) moved at a circular path between surface and 14 m depth, September 15, 1999. Top: biologically effective fluence rate for inhibition of photosynthesis E* inh , bottom: relative production P/P max Lesser (1991) speculated that a certain time period (in their experiments with a marine diatom ca. 30 min) is necessary to balance UV damage and repair mechanisms.…”
Section: Discussionmentioning
confidence: 99%